THE ADAPTATION PROCESS AND CHALLENGES OF EDUCATION EXPORT - Kurkisuo, Essi (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
The purpose of this study is to investigate the challenges of the adaptation process of education export. The research is conducted as a single case study that concentrates on three education export projects. The case company in the research is Team Academy. The study goes through the different forms of education export, the adaptation of education export and the challenges of the education export –process by means of theory and empirical data. The research is carried out as a qualitative research and the method used is a qualitative content analysis. More specifically the research is an abductive content analysis. The research data is collected in four in-depth interviews from Team academy representatives who have been strongly involved in certain education export –project of Team Academy. The research confirms the theory in the challenge of hierarchy, funding and registration issues, and refutes it in the challenge of competition, legislation, different governmental attitudes and knowledge in productization. The main challenges of the adaptation process are related to funding, differences in values, sudden changes, the complex nature of the learning model, concept of time, teamwork as method and accreditation. It is highlighted that in the future operations, anticipating problems that arise from for example cultural differences and differences in values, communication, managing the money flows and the company form is recommended. Future research could continue with investigating the suitable company form for education exports of this kind, and how to stand out and communicate when operating under another institution. It is considered a potential risk that a brand encloses the brand that operates under it.